1996
DOI: 10.1016/s1078-5884(96)80110-9
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil elastase, von willebrand factor, soluble thrombomodulin and percutaneous oxygen in peripheral atherosclerosis

Abstract: Our data support the hypothesis that release of elastase from activated neutrophils relates to endothelial cell damage. This may contribute to hypoxia and may result in the deterioration in clinically assessed atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…The means of total leukocyte count and counts of all leukocyte subtypes in the extreme hypertriglyceridemic group were all higher than those in the pure hypertriglyceridemic group, although only the differences in total leukocyte count and neu- trophil count reached statistical significances (see data in the last paragraph of the Results section). There is accumulating evidence from human studies that hypertriglyceridemia is a risk factor for atherosclerosis and CVD (6,7), and it seems likely that different leukocytes play different roles in atherogenesis (8)(9)(10)20). A higher peripheral total leukocyte count is associated with a higher risk of CVD (3,(11)(12)(13) and the association of hypertriglyceridemia with a higher CVD risk …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The means of total leukocyte count and counts of all leukocyte subtypes in the extreme hypertriglyceridemic group were all higher than those in the pure hypertriglyceridemic group, although only the differences in total leukocyte count and neu- trophil count reached statistical significances (see data in the last paragraph of the Results section). There is accumulating evidence from human studies that hypertriglyceridemia is a risk factor for atherosclerosis and CVD (6,7), and it seems likely that different leukocytes play different roles in atherogenesis (8)(9)(10)20). A higher peripheral total leukocyte count is associated with a higher risk of CVD (3,(11)(12)(13) and the association of hypertriglyceridemia with a higher CVD risk …”
Section: Discussionmentioning
confidence: 99%
“…There is little information concerning this issue so far in the literature. An in-depth study on this point may help in understanding the pathophysiology of hyperlipidemia-induced atherosclerosis, since accumulating evidence from human studies has shown that hyperlipidemia is a major cause of atherosclerosis and cardiovascular disease (CVD) (5)(6)(7), that different types of leukocytes are likely to play important but different roles in atherosclerosis (8)(9)(10), and that a higher peripheral total leukocyte count is associated with an increased incidence of CVD (3,(11)(12)(13). In addition, because cigarette smoking and obesity are frequently found in association with both lipid disorders (14-16) and a higher peripheral leukocyte count (1,3,13,(17)(18)(19), we included the factors of smoking and body mass index (BMI) in the study.…”
mentioning
confidence: 99%
“…These may contribute to diseases such as atherosclerosis, myocardial infarction, stroke and peripheral vascular disease, and may cause host cell damage following surgery involving the application of a tourniquet. 16,17 Previous studies have used animal and human models of ischaemia-reperfusion injury. [18][19][20][21] Leucocytes are involved intrinsically in the inflammatory reaction and thus deserve research attention.…”
Section: Introductionmentioning
confidence: 99%
“…16,28 Statistical analysis Results were presented as mean ± standard deviation (SD). Changes in the measured parameters during ischaemia and reperfusion were determined by repeated measures analysis of variance (ANOVA).…”
mentioning
confidence: 99%
“…There is abundant evidence that activation of this system occurs in chronic pulmonary disease [7,8] in which inflammation plays a role. More recently evidence has emerged that indicates that elastase activity may be related to endothelial cell damage [9] . This opens the door for an involvement in vascular disease and to support this, in a rat heart model, inhibition of neutrophil elastase was associated with cardioprotection from repetitive ischaemia and myocardial infarction [10] .…”
Section: See Page 1607 For the Article To Which This Editorial Refersmentioning
confidence: 99%